Macrophages Can Drive Sympathetic Excitability in the Early Stages of Hypertension - Neely, Oliver C.; Domingos, Ana I.; Paterson, David J. (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is a major health burden worldwide with many cases resistant to current treatments. Hyperactivity of the sympathetic nervous contributes to the etiology and progression of the disease, where emerging evidence suggests that inflammation may underpin the development of sympathetic dysautonomia. This study examined whether macrophages could drive the sympathetic phenotype in Spontaneously Hypertensive Rats (SHR) before animals develop high pressure. Stellate neurons from wild-type control Wistar rats and SHRs were co-cultured with blood leukocytes from their own strain, and also crossed cultured between strains. The calcium transient response to nicotinic stimulation was recorded using Fura-2 calcium imaging, where SHR neurons had a greater calcium transient compared with Wistar neurons. However, when co-cultured with leukocytes, Wistar neurons began to phenocopy the SHR sympathetic hyperactivity, while the SHR neurons themselves were unaltered. Resident leukocyte populations of the SHR and Wistar stellate ganglia were then compared using flow cytometry, where there was a shift in monocyte-macrophage subset proportions. While classical monocyte-macrophages were predominant in the Wistar, there were relatively more of the non-classical subset in the SHR, which have been implicated in pro-inflammatory roles in a number of diseases. When bone marrow-derived macrophages (BMDMs) were co-cultured with stellate neurons, they made Wistar neurons recapitulate the SHR nicotinic stimulated calcium transient. Wistar BMDMs however, had no effect on SHR neurons, even though SHR BMDMs increased SHR neuron responsiveness further above their hyper-responsive state. Taken together, these findings show that macrophages can be potent enhancers of sympathetic neuronal calcium responsiveness, and thus could conceivably play a role in peripheral sympathetic hyperactivity observed in the early stages of hypertension.